Psychometric testing : critical perspectives - Cripps, Barry, 1938- (West Sussex, UK : John Wiley and Sons, Inc. : Wiley-Blackwell, 2017)
Psychometric Testing offers an in-depth examination of the strengths and limitations psychometric testing, with coverage of diverse methods of test development and application. -A state-of-the-art exploration of the contemporary field of psychometric testing, bringing together the latest theory and evidence-based practice from 21 global experts -Explores a variety of topics related to the field, including test construction, use and applications in human resources and training, assessment and verification of training courses, and consulting -Includes applications for clinical psychology, performance psychology, and sport and exercise psychology across a range of professions (research, teaching, coaching, consulting, and advising) -Acknowledges the dynamic nature of the field and identifies future directions in need of more research, including Internet and smart phone testing.
Vendor-supplied metadata.
Keywords: Psychometrics; PSYCHOLOGY / Reference; Psychometrics; Electronic books